Representation of the Values of Friendship, Courage, and Self Confidence Contained in the Film Jumbo: A Semiotic Study by Roland Barthes - Ilafi Galah Sabrina; Anas Ahmadi (Raja Zulkarnain Education Foundation, 2026)
This study aims to describe the representation of the values of friendship, courage, and self confidence contained in the film Jumbo by Ryan Andriandhy through Roland Barthes’ semiotic study. This research was conducted on the animated film Jumbo which was released in 2025. The population in this study were all scenes in the film Jumbo, while the research sample was in the form of scene clips that display visual and verbal signs that represent the values of friendship, courage, and self-confidence. The research instrument in this study was the researcher himself as the main instrument with the help of a data classification table. The data collection technique was carried out through listening, reading, and taking notes by watching the film repeatedly, observing the scenes, and documenting relevant image clips. The data analysis tool used was Roland Barthes’ semiotic theory which includes three levels of meaning, namely denotation, connotation, and myth. The results of the study show that the film Jumbo represents the value of friendship through mutual support and solidarity between characters; the value of courage through the actions of characters in facing fear, conflict, and challenges; and the value of self confidence through the process of self-acceptance and the main character’s belief in his abilities.